INTEGRASI METAFISIKA ISLAM DAN SAINS - Sulhadi, Asep; Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2023)
Metaphysics, which principally contains the concept of studying the nature of something that lies behind physics or something spiritual in nature and cannot be explained by the rules of explanation found in science, has caused several experts to differ in opinion regarding its relation to science. There are circles that separate metaphysics and science. They view that science is real and has nothing to do with metaphysical matters such as not based on logic, irrational or unreal. Scholars regard metaphysics as pseudo problems whose discussion tends to be avoided. However, there are also some people who agree that metaphysics has a close relationship with science in several ways. In fact, according to these circles, history has recorded that metaphysics and science once had a close relationship in which both were considered as a unit and were in the same area, namely natural philosophy. In this simple paper, the author will discuss metaphysics and science, with the following research questions: first, are metaphysics and science interrelated and can be integrated. Second, is it possible that science will develop without metaphysics. Keywords: Meaphysics, Sains, al-Qur’an